Utilization of water and light resources by annual crops under semi-arid conditions when planted between Leucaena leucocephala (Lam.) de Wit hedgerows - Rethman, N.F.G. (University of Pretoria, 2013)
Dissertation (MSc(Agric) : Pasture Science)--University of Pretoria, 2008.